Attitudes of teachers toward evidence-based practices - Collins, Matthew (My University, 2018)
This study examined the attitudes of teachers toward evidence-based practices (EBPs) among Pre-K through 8th grade regular and special education teachers within rural schools in north central Wisconsin. Implementation of EBPs lags behind research in most disciplines, including agriculture, medicine, mental and behavioral health therapy, and education. Implementation science has developed around this phenomenon in recent years and will be used in the State of Wisconsin to increase the adoption of EBPs to address achievement gaps between students with and without disabilities. The Evidence-Based Practice Attitudes Scale was used to determine the level of willingness to adopt EBPs among rural school teachers. Correlations were studied between willingness to adopt EBPs and teacher characteristics of age, total years of service, years of service in their current school, years of service in their current position, size of student population, and educational attainment. Significant findings of this study were (a) a teacher’s age influences their perception of relevance of evidence-based practices, (b) years of service in a teacher’s current school influences their willingness to adopt required practices, and (c) the size of the student population influences a teacher’s openness to innovative practices. Implications for utilization of attitude measures for staff selection, readiness, and technical assistance determination were examined. Further research into educators’ attitudes towards EBPs will be necessary to establish educator attitude psychometric data.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Education - Educational Leadership and Policy Superintendent Licensure
Keywords: Education, Rural--United States; Teachers--United States--Attitudes